Topography and Morphology of a Hydrogel Enriched with Allantoin for Biomedical Purposes - Saucedo-Acuña, Rosa (2018)
The intention to obtain a biodegradable hydrogel enriched with allantoin is to conform a medium of distribution for this natural extract. In this case allantoin was distributed in two layers. One layer to be released immediately into the area of interest and in a second layer for prolonged action. It is known antibacterial and regeneration properties by allantoin, but until today we can only understand antibacterial mechanism, while its role of this extract in the regeneration process still not understood.